THE STATUS AND FUNCTION OF THE PROVINCIAL WAGE COUNCILS IN THE ARRANGEMENT OF THE PROVINCIAL MINIMUM WAGE IN THE PROVINCE OF WEST NUSA TENGGARA - Nugrahayu, Zainun Zakiya (Jurnal IUS (Kajian Hukum dan Keadilan), 2015)
This research intends to study the status and function of the provincial wage councils in the arrangement of the provincial minimum wage. This research uses both statutory and conceptual approach. The object of it is the regulation of the arrangement of provincial minimum wage. The resources of the research are statutes, books, papers and other supporting references which deductively and normatively analyzed. The result of the research shows the followings: firstly, the arrangement of the provincial minimum wage complies with the provisions stipulated in the Labor Act, even though specific government regulation on this matter has not been released yet.; Secondly, the provincial wage councils of the province of West Nusa Tenggara plays important role as agency technical functionary giving governor advice and consideration before he decides the provincial minimum wage. Yet, the recommendation given by the provincial wage councils has not any binding power or legal power in the arrangement of provincial minimum wage. The provincial wage council has not also coordinative authority with the wage councils at different level.Key words: the provincial minimum wage, the provincial wage councils.